2022
DOI: 10.2196/38015
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use for Research Participant Recruitment: Integrative Literature Review

Abstract: Background Social media tools have provided health researchers with the opportunity to engage with communities and groups in a nonconventional manner to recruit participants for health research. Using social media to advertise research opportunities and recruit participants facilitates accessibility to participants from broad geographical areas and diverse populations. However, little guidance is provided by ethics review boards for researchers to effectively use this recruitment method in their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 129 publications
(344 reference statements)
2
53
0
Order By: Relevance
“…However, the authors rightly noted that managing ethical and regulatory aspects will be necessary to take full advantage of this novel opportunity [62]. Darko et al published in their recent review a frst guideline to be used by ethical boards and research support services within academic institutions to provide guidance for researchers to efectively use this recruitment method [63].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors rightly noted that managing ethical and regulatory aspects will be necessary to take full advantage of this novel opportunity [62]. Darko et al published in their recent review a frst guideline to be used by ethical boards and research support services within academic institutions to provide guidance for researchers to efectively use this recruitment method [63].…”
Section: Discussionmentioning
confidence: 99%
“…The use of social media as a tool to promote research participation is increasing and has shown effectiveness in a number of observational studies and clinical trials, including those with hard-to-reach population [ 33 , 34 ]. Effective use of social media has also been a focus of our retention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The PACT participated in all stages of this study including setting priorities, determining research questions, and interpreting and communicating findings. The use of social media as a tool to promote research participation is increasing and has shown effectiveness in a number of observational studies and clinical trials, including those with hard-to-reach population [33,34]. Effective use of social media has also been a focus of our retention strategies.…”
Section: Plos Onementioning
confidence: 99%
“…This finding could be attributed to a healthy survivor bias. Furthermore, social media recruitment has had limited participation of older adults ( 48 ). With comparison of our previous study of newly diagnosed breast cancer patients in Maryland utilizing Maryland Cancer Registry data, the mean age at diagnosis was 58.2 years among Black women diagnosed between 2007 and 2017 ( 25 ), while the mean age at diagnosis for the current pilot study was 49.1 years.…”
Section: Discussionmentioning
confidence: 99%